Forging Just Climate Policies: Reconciling Justice Perceptions in Deliberative Mini‐Publics - Kulha, Katariina (Wiley, 2025)
Demands for ambitious climate measures have been accompanied by calls for a just transition, implying policies that take into account aspects of social justice in climate change mitigation. In many countries, deliberative mini-publics, such as Citizens' Assemblies and Citizens' Juries, have been convened to develop recommendations for socially just climate policies. While experimental studies have established individuals' propensity for outcome favorability in fairness assessments, proponents of deliberative mini-publics maintain that deliberation helps launder self-interested views and produces so-called meta-consensus regarding values, beliefs, and preferences. However, deliberative mini-publics' capability to advance shared interpretations of justice in the context of climate policies has been scarcely examined. To complement this gap, this paper researches two Citizens' Juries, organized in Finland, which discussed fairness of climate policies in the fields of transport and forest use. The study applies Q methodology to map jurors' subjective justice perceptions at the beginning and at the end of the juries. Changes in the perceptions are then examined to assess whether deliberation induces the acknowledgment of the divergent notions of justice. The findings indicate, firstly, that deliberative mini-publics can enhance consensus on vulnerabilities that should be considered in policy-making. Secondly, deliberative mini-publics can help to clarify the key conflicts in perceptions of justice, even when meta-consensus on the different perceptions would not be attained.